Dyslipidemia in Critical Conditions of Various Etiology - L. N. Shcherbakova; L. V. Molchanova; S. V. Malakhova (Общая реаниматология, 2008)
Objective: to establish the common regularities and etiological features of lipid metabolic changes in critical conditions of various etiology. Subjects and materials: 102 patients with sepsis, severe mechanical injury, and moderate gestosis were examined. The patients were divided into groups according to the etiology and severity of a condition. The patients’ age was also kept in mind in severe mechanical injury. The plasma concentrations of triglycerides (TG), total cholesterol, high-density lipoprotein cholesterol (HDLC), low-density lipoprotein cholesterol (LDLC), and very low-density lipoprotein cholesterol (VLDLC) were determined. Results. There were atherogenic changes in lipid metabolism, which were characterized by a rise in the level of TG and accordingly VLDLC with decreased HDLC concentrations. In sepsis and gestosis, the changes in TG and VLDLC levels occurred in the range of the concentrations exceeding the physiological normal values. In sepsis, the positive changes in these parameters were associated with a good clinical outcome. In mechanical injury, the increase in TG and VLDLC levels occurred in the physiological normal range and it was more significant in fatal outcome. Conclusion. Atherogenic changes in lipid metabolism are a common regularity in critical conditions, they are characterized by an increase in TG and VLDLC levels with decreased HDLC concentrations, show various trends, and occur in different ranges of concentrations depending on the etiology and severity of a condition. Key words: dyslipidemia, atherogenesis, critical conditions, severe mechanical injury, gestosis, sepsis.